2009
DOI: 10.1111/j.1525-1594.2009.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Real‐Time Monitoring of Gaseous Microemboli in Pediatric Cardiopulmonary Bypass

Abstract: We describe the occurrence and distribution of gaseous microemboli with real-time monitoring in a pediatric cardiopulmonary bypass (CPB) circuit and in the cerebral circulation of patients using the Emboli Detection and Classification (EDAC) system and transcranial Doppler (TCD). Four patients (weights 3.2-13.8 kg) were studied. EDAC monitors were located on the venous line and on the postfilter arterial line to measure gaseous microemboli in the CPB circuit. TCD was used to measure high-intensity transient si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Although present findings support the conclusion that pulsatile flow has distinct advantages over nonpulsatile flow in brain protection during CPB, at least at advanced time points (24) or emboli detection and classification (EDAC) quantification (25), measures which may have enhanced results obtained. TCD data indicated that nonpulsatile rather than pulsatile perfusion resulted a lower decrease in PI at the before XC time point, which may possibly have been because of the variances in hemodynamic stability as surgical teams prepared for XC administration.…”
Section: Discussionsupporting
confidence: 39%
“…Although present findings support the conclusion that pulsatile flow has distinct advantages over nonpulsatile flow in brain protection during CPB, at least at advanced time points (24) or emboli detection and classification (EDAC) quantification (25), measures which may have enhanced results obtained. TCD data indicated that nonpulsatile rather than pulsatile perfusion resulted a lower decrease in PI at the before XC time point, which may possibly have been because of the variances in hemodynamic stability as surgical teams prepared for XC administration.…”
Section: Discussionsupporting
confidence: 39%
“…In our operating room, two Emboli Detection and Classification (EDAC) probes are inserted into the venous and arterial lines to monitor GME entry into the circuit and delivery to the patient. Our clinical studies demonstrated that the venous line is the main source of GME, particularly when using VAVD (21,22). The negative pressure in the venous reservoir added by VAVD may increase the formation and delivery of GME.…”
Section: Clinical Gme Monitoringmentioning
confidence: 99%
“…wang et al observed that GMe were detected in the arterial line during volume administration both before and after cPB. they concluded the circuit priming technique should be optimized to eliminate GMe in the extracorporeal circuit before cPB (33). cO 2 flushing of the empty circuit and arterial line filter decrease the number of gaseous emboli in the prime compared with a conventional circuit that contains air before being primed with fluid (92,93).…”
Section: Generation Detection and Prevention Of Gaseous Microembolimentioning
confidence: 99%
“…Most tcd systems utilize pulsed-wave ultrasound to detect cerebral emboli based on the measurement of the backscatter from the emboli. when microemboli are detected, brief transient increases in the ultrasonic signal are generated and recorded as HItS (33). the vast majority of published literature relating to embolus detection concerns tcd ultrasound in which a 1 MHz to 2 MHz probe is placed over the temporal lobe of the head in order to insonate the McA (34).…”
Section: Transcranial Cranial Doppler (Tcd)mentioning
confidence: 99%